A Raspberry Pi-based, RFID-equipped birdfeeder for the remote monitoring of wild bird populations. Issue 1 (2nd January 2019) - Youngblood, Mason
ABSTRACT: Radio-frequency identification (RFID) is an increasingly popular wireless technology that allows researchers to monitor wild bird populations from fixed locations in the field. I have developed an RFID-equipped birdfeeder based on the Raspberry Pi Zero W, a low-cost single-board computer, that collects continuous visitation data from birds marked with passive integrated transponder (PIT) tags. Each birdfeeder has a perch antenna connected to an RFID-reader board on a Raspberry Pi powered by a portable battery. When a tagged bird lands on the perch to eat from the feeder, its unique code is stored with the date and time on the Raspberry Pi. These birdfeeders require only basic soldering and coding skills to assemble, and can easily be outfitted with additional hardware like video cameras and microphones. I outline the process of assembling the hardware and setting up the operating system for the birdfeeders. Then, I describe an example implementation of the birdfeeders to track House Finches Haemorhous mexicanus on the campus of Queens College in New York City.